Studi Perancangan Instalasi Penerangan dan Pengkondisi Suhu Ruangan Pada Gedung Bertingkat Las Mesin - Vicky Prasetia; Erna Alimudin; Purwiyanto Purwiyanto; Muhamad Yusuf; Mohammad Nurhilal (P3M Politeknik Negeri Cilacap, 2023)
Lighting is one of the most important requirements of a building. This is because inadequate lighting of a space can affect the health and comfort of activities in that space. In addition to less important lighting, room temperature adjustments, room temperature adjustments have a significant impact on comfort during activities in the room. This magazine describes the lighting and room temperature control design of the CilacapState Polytechnic Welder Shop. The method used in this study is a quantitative method. This method calculates the required lighting and room temperature control and compares it with the standards. 2 rooms increase the number of light points and 3 rooms change the type of lamp with a higher lumen. There are 8 rooms that are recommended to use air conditioners with SNI 91714189. According to the SNI, the number of air conditioners and the capacity of air conditioners adjusts to the size of the room.